Enhancing organizational health literacy in a rural Missouri clinic: a qualitative case study. Issue 5 (10th June 2019) - Wray, Ricardo; Weaver, Nancy; Adsul, Prajakta; Gautam, Kanak; Jupka, Keri; Zellin, Stacie; Goggins, Kathryn; Vijaykumar, Santosh; Hansen, Natasha; Rudd, Rima
Abstract : Purpose: The purpose of this paper is to evaluate a collaborative effort between a health care organization and academic institution to strengthen organizational health literacy. Design/methodology/approach: The intervention took place at a rural, federally qualified health clinic in Missouri between May 2009 and April 2011. Qualitative interviews of key informants were conducted before ( n =35) and after ( n =23) the intervention to examine program implementation and success in effecting organizational change. Findings: Intervention activities helped establish a comprehensive understanding of health literacy. The project achieved moderate, fundamental and sustainable organizational change. The program successfully integrated health literacy practices into clinic systems and garnered leadership and organizational commitment, helped the workforce improve interpersonal communication and embedded practices making health education materials more accessible. Originality/value: The study points to programmatic, conceptual and methodological challenges that must be addressed for organizations to improve health literacy practices, and suggests change management strategies to advance organizational health literacy.